Nutritional profile of narcotic users in treatment in a northeast region (Research, Society and Development, 2020)
Introduction: Drug abuse is a relevant public health problem. In view of the harm caused to users by the abuse of these substances. Objective: To know the nutritional profile of drug addicts in treatment, in order to contribute to an effective nutritional care. Method: Anthropometric data (weight and height) were collected to evaluate Body Mass Index, and a food frequency questionnaire was applied to verify their eating habits. Results: Most of the individuals under treatment were between 31 and 40 years old, and were eutrophic. There were some cases of overweight and only one individual had obesity, which can be explained by the increased consumption of energy foods to the detriment of low consumption of fruits and vegetables. Conclusion: The nutritional profile of drug addicts undergoing treatment in the institution evaluated ranged from eutrophic to overweight, suggesting a higher intake of food, possibly replacing the drug, as a compensation.